IDENTIFICATION OF EXTREME SEA LEVELS AND CONCURRENT MARINE HEATWAVES-EXTREME SEA LEVELS IN SETIO WATERS 1993-2022 - Claudia Boedihardjo, Denise
The continuously increasing global warming triggers an increase in sea surface temperatures. The rise in sea surface temperatures affects various parameters, particularly sea levels. When extreme sea level (ESLs) events coincide with MHWs events, a phenomenon known as CHESLs (Concurrent Marine Heatwaves-Extreme Sea Levels/CHESLs) emerges with greater impact. This study aims to identify ESLs and CHESLs events in the Southeastern Tropical Indian Ocean (SETIO), which includes the waters off the western coast of Sumatra, southern Java, and Nusa Tenggara, over the period of 1993–2022 (30 years). The research focuses on four station locations: Padang (location A), Cilacap (location B), Prigi (location C), and Benoa (location D). The primary data used are sea level anomaly (SLA) and sea surface temperature anomaly (SSTA) obtained from satellite altimetry. The analysis method employed is statistical. The analysis results indicate a positive linear trend of SLA and SSTA with varying values at each location. Over the 30 years, 22 ESL events and 4 CHESL events were identified in Padang, 16 ESL events and 4 CHESL events in Cilacap, 18 ESL events and 4 CHESL events in Prigi, and 23 ESL events and 4 CHESL events in Benoa. ESLs predominantly occur when the Australian monsoon is active during the DJF period (45%), the La Niña phase (76%), and N-IOD (40%). CHESLs predominantly occur when the Indian monsoon is active during the MAM period (53%), the La Niña phase (76%), and N-IOD (82%). The influence of N-IOD is more dominant at the Padang station. Conversely, the influence of La Niña is more dominant at the Cilacap, Prigi, and Benoa stations. ESLs events are more frequently found in onshore areas, while CHESLs are more frequently found in offshore areas. The total frequency of ESLs and CHESLs events has increased by 66.7% over the last decade.